Supremely partisan how raw politics tips the scales in the United States Supreme Court - Zirin, James D. (Rowman & Littlefield, 2016)
"On the eve of a presidential election that may determine the makeup of Supreme Court justices for decades to come, prominent attorney James D. Zirin argues that the Court has become increasingly partisan, rapidly making policy choices right and left on bases that have nothing to do with law or the Constitution. Zirin explains how we arrived at the present situation and looks at the current divide through its leading partisans: Justices Ruth Bader Ginsburg and Sonia Sotomayor on the left and Clarence Thomas and the late Antonin Scalia on the right. He also examines four of the Court's most controversial recent decisions: Hobby Lobby, Obamacare, gay marriage, and capital punishment, arguing that these politicized decisions threaten to undermine public confidence in the Supreme Court"--Book jacket.